Dieulafoy's Lesion Associated with Megaesophagus - Valdemir José Alegre Salles; Rafael Borges Resende; Gustavo Seiji; Rodrigo Correia Coaglio (Archives of Clinical Gastroenterology - Peertechz Publications, 2020)
A 31-years-old male patient, with no previous symptoms, admitted to the ER with massive hematemesis that started about 2 hours ago and already with hemodynamic repercussions. After initial care with clinical management for compensation, and airway protection (intubation) he underwent esophagogastroduodenoscopy (EGD), which was absolutely inconclusive due to the large amount of solid food remains and clots already in the proximal esophagus with increased esophageal gauge.